A Conceptual Framework for Enabling Risk in Inclusive Postsecondary Education Programs. Issue 3 (August 2022) - Rooney-Kron, Magen; Regester, April; Lidgus, Jonathan; Worth, Christopher; Bumble, Jennifer L.; Athamanah, Lindsay S.
More students with intellectual and developmental disability (IDD) are attending post-secondary education than ever before. As more students with IDD enter college, inclusive post-secondary education programs (IPSE) will be required to make important decisions about the types of services and supports they provide. IPSE program staff should aim to provide supports and services that honor students' dignity of risk and facilitate opportunities for students to take risks. The purpose of this article is to describe a conceptual framework IPSE program staff can use to assess the extent to which the supports and services they provide enable risk-taking opportunities for students in their program. The framework includes five steps: identify areas for growth, understand risks and rewards for students and stakeholders, evaluate natural supports and determine appropriate supplemental supports, identify and enable access to natural consequences, and reflect and plan for more authentic risk. An example of how to use the framework in the context of residential housing will be described.